How automatic identification system (AIS) antenna setup affects AIS signal quality. (15th May 2015) - Last, Philipp; Hering-Bertram, Martin; Linsen, Lars
Abstract: The AIS is mostly used to exchange different vessel data between vessels and AIS base stations. For mariners AIS data have become a useful complement to radar data since manual collision avoidance is supported by providing additional information via AIS. Furthermore AIS allows for implementing course prediction algorithms. However, AIS message losses have been confirmed by several studies affecting and restricting the AIS usage especially within vessel prediction algorithms. Several evaluations and simulations concerning the Self-Organized Time Division Multiple Access (SOTDMA) algorithm show that an AIS message loss caused by system overload is unlikely. However, in contrast to the SOTDMA evaluations there are no evaluations about the influence of the VHF medium and the AIS antenna setup on the AIS reception rate. Therefore, we intend to identify the VHF influence on the reception rate by using high quality AIS hardware and AIS antenna installations according to IMO guidelines to record and evaluate AIS data on a German Search and Rescue vessel. By using two different antennas we evaluate the meaning of the antenna height as well as of the general antenna setup for the AIS message reception rate and show the impact of measured reception rates for vessel prediction algorithms. Highlights: We evaluate the VHF influence on the AIS reception rate using high quality hardware. Only a small percentage of lost messages are caused by collisions. The main reason for an AIS message loss is the AIS antenna setup. Additional reasons restricting the reception rate are environmental conditions. Stand-alone AIS data are not sufficient for current real-time tracking algorithms.